2018
DOI: 10.3390/f9050271
|View full text |Cite
|
Sign up to set email alerts
|

How Forest Gap and Elevation Shaped Abies faxoniana Rehd. et Wils. Regeneration in a Subalpine Coniferous Forest, Southwestern China

Abstract: Abstract:Focusing on the underlying ecological mechanisms of dominant species regeneration in forest gaps at a landscape scale can provide detailed understanding for gap-based forest management. The individual effects of forest gaps or elevation on the regeneration of Abies faxoniana Rehd. et Wils. are well known, although elucidating how gap characteristics and elevation concurrently influence regeneration remains an important challenge. In this paper, we present an explorative study using structural equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…In our case, the above-and below-ground environmental factors and the α-diversity and β-diversity were closely associated with forest gap and elevation, either directly or indirectly; however, these variables did not affect forest gap and elevation. Next, we compared all hypothesized candidate models with significant pathways, and we searched for a model that displayed a better fit to the observed data using the smallest AIC (Akaike's information criterion) (Kubota et al, 2004;Chen et al, 2018). Finally, the direct effects, indirect effects, and total effects of forest gaps and elevation on the diversity of the subalpine coniferous forest were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, the above-and below-ground environmental factors and the α-diversity and β-diversity were closely associated with forest gap and elevation, either directly or indirectly; however, these variables did not affect forest gap and elevation. Next, we compared all hypothesized candidate models with significant pathways, and we searched for a model that displayed a better fit to the observed data using the smallest AIC (Akaike's information criterion) (Kubota et al, 2004;Chen et al, 2018). Finally, the direct effects, indirect effects, and total effects of forest gaps and elevation on the diversity of the subalpine coniferous forest were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most likely explanations is that most species find it difficult to adapt to the extreme environment at high elevations. Thus, a low-intensity logging disturbance should be considered as a viable method used to maintain the abundance of canopy trees, which can protect the regeneration of tree seedlings and smaller plants from the harsh weather more than large canopy openings can (Chen et al, 2018).…”
Section: Forest Gap Effects On α-And β-Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…The mean annual rainfall is between 861 mm and 1800 mm, with the highest precipitation month of August averaging 340 mm. The soil is brown coniferous forest soil and the pH is between 3.9 to 5.0 (Chen et al 2018). The majority of the snowfall occurs from October to February at high elevation.…”
Section: Study Sitementioning
confidence: 99%
“…The majority of the snowfall occurs from October to February at high elevation. More detailed information on the study area could be found in our earlier publications (Chen et al 2018, Chen et al 2019).…”
Section: Study Sitementioning
confidence: 99%